The phenomenon of intrapartum transfer from a Western Australian birth centre to a tertiary maternity hospital: The experiences of women, partners and midwives - Kuliukas, Lesley Jane (Curtin University, 2017)
A descriptive phenomenological study was carried out in 2013-2014, to describe the experiences of women, partners and midwives when transfer in labour took place from a birth centre to an obstetric unit. Analysis of 48 interviews, using Giorgi’s method of thematic analysis, revealed unique and shared experiences, both positive and negative, which can now inform midwives, empowering them to better support parents whose plans for labour do not eventuate as they originally anticipated